2017
DOI: 10.1128/aac.00129-17
|View full text |Cite
|
Sign up to set email alerts
|

Moraxella Species as Potential Sources of MCR-Like Polymyxin Resistance Determinants

Abstract: Plasmid-mediated resistance to polymyxins mediated by the MCR-1/2 determinants has been reported in Enterobacteriaceae worldwide. Using PCR-based and cloning strategies, a series of Moraxella spp. were screened for mcr-like genes. Moraxella spp. that are mainly animal pathogens but may also be human pathogens were identified as potential reservoirs of mcr-like genes.KEYWORDS polymyxin, plasmid, resistance, reservoir, animal, MCR R esistance to polymyxins in Enterobacteriaceae results mostly from chromosomal mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

9
95
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 84 publications
(114 citation statements)
references
References 40 publications
(50 reference statements)
9
95
1
2
Order By: Relevance
“…1 We recently showed that some Moraxella species might constitute putative reservoirs of MCR-like proteins, with corresponding genes located on the chromosome of these species. 6 Hence, MCRlike proteins were identified in Moraxella catarrhalis, Moraxella lincolnii, Moraxella porci and Moraxella osloensis. They all share significant amino acid identities with MCR-1 and MCR-2, ranging from 59% to 64%.…”
mentioning
confidence: 95%
See 3 more Smart Citations
“…1 We recently showed that some Moraxella species might constitute putative reservoirs of MCR-like proteins, with corresponding genes located on the chromosome of these species. 6 Hence, MCRlike proteins were identified in Moraxella catarrhalis, Moraxella lincolnii, Moraxella porci and Moraxella osloensis. They all share significant amino acid identities with MCR-1 and MCR-2, ranging from 59% to 64%.…”
mentioning
confidence: 95%
“…Internal outward primers were then designed and used for an inverse PCR strategy, as previously performed. 6 The sequence of the entire mcr gene was thus obtained and it revealed that this new enzyme (termed MCR-2.2) was almost identical to MCR-2 (99% amino acid identity), with only 8 amino acid differences out of the 538 constituting the MCR-2 enzyme, and shared 82% amino acid identity with MCR-1.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…This work confirms previous hypotheses (12) that the mcr-1 gene had been initially mobilized by two copies of ISApl1 from an unknown progenitor, targeting broad-host range plasmid(s) that subsequently transferred this resistance gene into Enterobacteriaceae. Interestingly, our very recent work showed that Moraxella species are natural sources of mcr-like genes, and may harbor ISApl1 elements (21). Therefore, mobilization of the mcr-1 gene might have occurred into a Moraxella species (still to be precisely identified) through an ISApl1-mediated transposition process.…”
mentioning
confidence: 99%